Palladium-coated nanocomposite on tapered optical fiber for hydrogen sensing applications - Mohammed, Al-Khabet Mohammed Majeed (2022)
Gaseous pollutants such as hydrogen gas (H2) are present in daily human activities and have been studied extensively due to their high explosive and widespread use in many fields. A common H2 gas detector is electrically based. Although these electrical or conductometric sensors attain high sensitivity, they suffer from drawbacks, including poor selectivity, high operating temperature, and susceptibility to electromagnetic interference, which the optical-based sensor can improve. Optical fiber sensors offer advantages over electrical sensors in certain aspects, such as their compact size, the ability to work in harsh environments, and the ability for remote and distributed sensing. However, H2 detection with optical fibers has not been fully explored. Nanotechnology-enabled chemical sensors have been increasingly used to enhance the sensing performance compared to the conventional sensors toward target analytes owing to their high surface area. The sensing layer based on nanostructures has been identified to work at low temperatures with high sensitivity. Therefore, this research project aims to design and comprehensively analyze optical fiber-based H2 gas sensors by incorporating different nanocomposite coatings as sensing layers. This study uses tapered multimode silica fiber (MMF) sensors as a transducing platform. The tapering process is essential to improve the sensitivity to the environment through the interaction of the evanescent field over the area of the tapered surface area. The tapered area is coated with a sensor layer which is also an essential factor affecting the sensor's performance. The influence of nanostructures’ morphology and roughness on the sensing performance were also studied in this Ph.D. research. The nanostructured materials investigated are graphene oxide (GO), polyaniline (PANI), and molybdenum trioxide (MoO3). These nanomaterials were combined as a nanocomposite sensing layer to enhance the H2 detection. A noble metal, palladium (Pd), was selected as a catalyst to split hydrogen ions. The novel nanocomposites of Pd/GO, Pd/PANI/GO, and Pd/MoO3/PANI were dropped cast on the tapered optical fiber for sensing analysis. Combining these materials as nanocomposite adds up the functionality to enhance the high surface area to volume ratio to effectively miniaturize and improve the sensing properties of the developed sensors. In this context, nanocomposite materials promote effective H2 gas sensing peculiarity and allow the developed sensors to be operational at low temperatures. Micro-nano characterization techniques such as FESEM, EDX, AFM, and XRD were utilized to obtain detailed structural properties of these nanostructures and fundamentally understand their functions concerning optical sensor performance. The response of the sensors towards H2 gas was measured at concentrations of 0.125% - 2.00% using optical absorbance change within the wavelength range of 550-850 nm at different temperatures. The sensor performance was evaluated regarding response time, recovery time, sensitivity, repeatability, and stability at different temperatures. The developed H2 sensors using tapered optical fiber coated with Pd/GO, Pd/PANI/GO, and Pd/MoO3/PANI nanocomposite operated at different temperatures are the first of its kind according to the author’s knowledge. The Pd/GO nanocomposite-based sensor demonstrated higher sensitivity of about 33.22/vol% compared to Pd/PANI/GO and Pd/MoO3/PANI nanocomposite, where the sensitivity is about 10.43/vol% and 16.81/vol%, respectively. The response and recovery time of the developed sensors based on Pd/GO, Pd/PANI/GO, and Pd/MoO3/PANI nanocomposite recorded were 48 s, 60 s, and 90 s, and their recovery times were 420 s, 190 s, and 230 s, respectively. Overall, the developed sensor based on Pd/GO nanocomposite showed excellent sensitivity, higher response time, selectivity, and long-term stability compared to Pd/PANI/GO and Pd/MoO3/PANI nanocomposite-based sensors.